Identification of Potent and Safe Antiviral Therapeutic Candidates Against SARS-CoV-2 - Xiao, Xia; Wang, Conghui; Chang, De; Wang, Ying; Dong, Xiaojing; Jiao, Tao; Zhao, Zhendong; Ren, Lili; Dela Cruz, Charles S.; Sharma, Lokesh; Lei, Xiaobo; Wang, Jianwei (Frontiers in Immunology, 2020)
COVID-19 pandemic has infected millions of people with mortality exceeding 300,000. There is an urgent need to find therapeutic agents that can help clear the virus to prevent the severe disease and death. Identifying effective and safer drugs can provide with more options to treat the COVID-19 infections either alone or in combination. Here we performed a high throughput screen of approximately 1700 US FDA approved compounds to identify novel therapeutic agents that can effectively inhibit replication of coronaviruses including SARS-CoV-2. Our two-step screen first used a human coronavirus strain OC43 to identify compounds with anti-coronaviral activities. The effective compounds were then screened for their effectiveness in inhibiting SARS-CoV-2. These screens have identified 24 anti-SARS-CoV-2 drugs including previously reported compounds such as hydroxychloroquine, amlodipine, arbidol hydrochloride, tilorone 2HCl, dronedarone hydrochloride, and merfloquine hydrochloride. Five of the newly identified drugs had a safety index (cytotoxic/effective concentration) of >600, indicating wide therapeutic window compared to hydroxychloroquine which had safety index of 22 in similar experiments.Mechanistically, five of the effective compounds were found to block SARS-CoV-2 S proteinmediated cell fusion. These FDA approved compounds can provide much needed therapeutic options that we urgently need in the midst of the pandemic.